Epistemology of Contemporary Islamic Education - Achmad Jasuli Afandi; Moh. Affan; Hasbullah; Madlubur Rhisky; Muhamad Zaenal Abidin; Rahmat Zubandi Thahir; Abd. Somad (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
This study aims to analyze the epistemological crisis in contemporary Islamic education, characterized by the dichotomy between religious knowledge (naqliyah) and general knowledge (aqliyah), and to formulate an integrative epistemological reconstruction model. The study uses a qualitative approach based on a systematic literature review by analyzing various relevant academic sources. The results of the study indicate that the epistemological dichotomy has led to the disintegration of science and the weakening of the orientation of Islamic education. A comparison of the thoughts of Ismail Raji al-Faruqi and M. Amin Abdullah reveals that the Islamization of science emphasizes the normative foundation of monotheism, while integration-interconnection emphasizes a dialogical and multidisciplinary approach. The synthesis of the two is strengthened through the integration of bayani, burhani, and irfani epistemologies that can build a holistic and anti-dichotomous scientific paradigm. However, the implementation of this paradigm still faces obstacles in the methodological and practical aspects of education. Therefore, the reconstruction of the epistemology of Islamic education needs to be directed at strengthening the integrative curriculum, transforming the role of educators, and responding to global issues. This research contributes to offering an integrative epistemological framework that is not only theoretical, but also transformative in responding to the challenges of modernity.